2017
DOI: 10.1016/j.biomaterials.2017.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale design and synthesis of biomimetic gradient protein/biosilica composites for interfacial tissue engineering

Abstract: Continuous gradients present at tissue interfaces such as osteochondral systems, reflect complex tissue functions and involve changes in extracellular matrix compositions, cell types and mechanical properties. New and versatile biomaterial strategies are needed to create suitable biomimetic engineered grafts for interfacial tissue engineering. Silk protein-based composites, coupled with selective peptides with mineralization domains, were utilized to mimic the soft-to-hard transition in osteochondral interface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 85 publications
0
44
0
Order By: Relevance
“…Some tissues in the body present pronounced gradients in ECM composition and/or cell population, particularly those at interfaces such as the osteochondral interface, the ligament‐to‐bone interface, and the tendon‐to‐bone insertion site . Conventional methods rely on the use of anisotropic scaffolds containing distinctive or continual sections with properties matching those in the native tissues to be engineered .…”
Section: Emerging Evolutions In Bioprintingmentioning
confidence: 99%
“…Some tissues in the body present pronounced gradients in ECM composition and/or cell population, particularly those at interfaces such as the osteochondral interface, the ligament‐to‐bone interface, and the tendon‐to‐bone insertion site . Conventional methods rely on the use of anisotropic scaffolds containing distinctive or continual sections with properties matching those in the native tissues to be engineered .…”
Section: Emerging Evolutions In Bioprintingmentioning
confidence: 99%
“…The whole free‐standing protein system can be removed from the container and used for further post‐processing (Figure d). Our previous studies revealed that the positively charged amino acids dominated the silicification process, while the silk is negative charged . As a result, the silica nanoparticles grew selectively on the R5 peptide patterned surface, represented by the schematic drawing and confirmed by optical imaging and scanning electron microscopy (SEM) (Figure e).…”
Section: Resultsmentioning
confidence: 61%
“…The biosilica selective peptide‐R5, a bioinspired analog derived from the silaffin peptides that are used for silicification in Cylindrotheca fusiformis , was selected for the peptide ink since it can directly serve as a trapping agent to trigger the site‐specific in vitro silicification (Figure c). Our previous studies indicated that enzymatic cross‐linking between the silk and R5 molecular chains allowed for tight bonding between the substrate and printed peptide patterns . A freshly printed 1.2 cm wide peptide logo with micrometer resolution was visually discernable from the transparent underlying silk hydrogel ( Figure a).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations